Corrosion observation method for TiNi alloy grain structure

By designing specific corrosion solution components and field observation methods, the grain boundaries of TiNi alloys are shown, which solves the problems that are difficult to assess in the prior art, and realizes accurate assessment of grain size and a safe and easy-to-operate corrosion observation process.

CN119290882APending Publication Date: 2025-01-10西安汉唐分析检测有限公司
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411498966.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-25
Publication Date
2025-01-10

AI Technical Summary

Technical Problem

The prior art lacks a unified corrosive agent to show the microstructure and grain structure of Ti-Ni alloys, making it difficult to accurately evaluate grain size.

Method used

By designing specific corrosion solution components, including aqua regia, hydrofluoric acid, nitric acid and concentrated sulfuric acid, the proportion and etching time of corrosion solutions are controlled, so that the TiNi alloy can show obvious grain boundaries and no obvious corrosion under a metallographic microscope. The pit was evaluated by the field observation method.

Benefits of technology

The crystal structure of TiNi alloy is clearly manifested and accurately evaluated, and the problem of difficult grain boundaries in the prior art is solved. The method is easy to operate, the reagent is non-toxic and easy to promote.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119290882A_ABST
    Figure CN119290882A_ABST
Patent Text Reader

Abstract

The invention discloses a corrosion observation method for a TiNi alloy grain structure. The method comprises the following steps: 1, machining a TiNi alloy to obtain a grain structure observation plane, grinding and washing; 2, carrying out mechanical polishing until the surface of the grain structure observation plane is free of scratches and dragging; 3, immersing into an etchant solution to erode; and 4, observing the grain structure under a metallographic microscope. According to the method, after the TiNi alloy is machined to form the grain structure observation plane, grinding, washing, mechanical polishing and corrosion solution erosion are sequentially carried out, so that the grain structure in the TiNi alloy is clearly and effectively shown, obvious grain boundaries exist, no obvious corrosion pits exist, and therefore the grain structure can be easily observed in a transparent field observation mode; the method is easy to operate, reagents and the process are non-toxic, the grain structure of the TiNi alloy can be clearly observed, no special equipment is needed, and the method is easy to popularize.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of metal material grain structure observation, and in particular relates to a corrosion observation method for TiNi alloy grain structure. Background Art

[0002] Shape memory alloy is a new functional material developed in the 1970s. Among them, Ti-Ni alloy has excellent shape memory properties and superelastic properties, and also exhibits good damping properties, corrosion resistance and biocompatibility. It has been widely used in aerospace, machinery, energy, electronics, medicine and daily life. Ti-Ni alloy usually needs to observe the alloy microstructure and evaluate the average grain size level in order to accurately evaluate the organization of Ti-Ni alloy.

[0003] Currently, there is no unified etchant for Ti-Ni alloys to display the microstructure and grain structure for the evaluation of grain size results. Summary of the invention

[0004] The technical problem to be solved by the present invention is to provide a corrosion observation method for the grain structure of TiNi alloy in view of the above-mentioned deficiencies of the prior art. The method controls the composition and proportion of the corrosive solution so that the grain structure in the TiNi alloy is clearly and effectively displayed, with obvious grain boundaries and no obvious corrosion pits, so that it is easy to observe the grain structure by open field observation and evaluate the grain size results, solving the problem that the existing Ti-Ni alloy has no unified corrosive agent for displaying the microstructure and grain structure for evaluating the grain size results.

[0005] In order to solve the above technical problems, the technical solution adopted by the present invention is: a corrosion observation method of TiNi alloy grain structure, characterized in that the method comprises the following steps:

[0006] Step 1, machining a TiNi alloy to obtain a grain structure observation plane, then grinding the machined grain structure observation plane on a metallographic grinder, and washing away the sand on the grain structure observation plane after grinding;

[0007] Step 2: placing the grain structure observation plane washed away from the sand in step 1 on a polishing machine for mechanical polishing until there are no scratches or drag on the surface of the grain structure observation plane;

[0008] Step 3, immersing the mechanically polished grain structure observation plane in step 2 into a corrosive solution for 5s to 20s;

[0009] Step 4: Place the grain structure observation plane after etching in step 3 under a metallographic microscope, and observe the grain structure by open field observation.

[0010] TiNi shape memory alloy is a TiNi intermetallic compound with shape memory effect, which is almost not corroded in conventional titanium alloy corrosive agent (mixed acid solution of hydrofluoric acid and nitric acid), and is also almost not corroded by Ni alloy corrosive agent (composed of hydrochloric acid and copper salt). In the research process of the present invention, it is found that aqua regia has a strong corrosive effect on Ni alloy, and titanium alloy is generally corroded by hydrofluoric acid, so the composition of the corrosive solution is designed, and the aqua regia ratio is adjusted, and hydrofluoric acid is added to achieve corrosion of TiNi alloy, but the grain boundary generated by corrosion of TiNi alloy is not obvious; therefore, sulfuric acid is further added, on the one hand, the reaction rate of the corrosive solution and the alloy is accelerated during erosion, and on the other hand, the corrosiveness of the corrosive solution is enhanced, so that the strong corrosive solution produces uneven corrosion on the TiNi alloy, the grain boundary corrosion rate is fast, and the internal structure of the grain is slow. After corrosion for a suitable time, the grain boundary corrosion is deeper, and the grain boundary shows a darker color under an optical microscope, and then the grain structure of the TiNi alloy can be observed.

[0011] The above-mentioned method for observing the corrosion of TiNi alloy grain structure is characterized in that the specific process of grinding in step 1 is: using a particle size of 120 # , 400 # , 800# and 1000 # The metallographic water sandpaper is used for grinding step by step. Each time the metallographic water sandpaper is changed for grinding, the grinding direction is turned 90° to ensure that the previous grinding marks are completely eliminated.

[0012] The above-mentioned corrosion observation method for the grain structure of a TiNi alloy is characterized in that the mechanical polishing in step 2 is first polished using a diamond suspension with a particle size of 10 μm, and then polished using a SiO2 suspension with a particle size of 0.5 μm.

[0013] The above-mentioned corrosion observation method of TiNi alloy grain structure is characterized in that the corrosion solution described in step 3 is composed of the following components in volume fractions: 1 to 2 parts of HF with a mass fraction of more than 40%, 0.5 to 2 parts of HNO3 with a mass fraction of 65% to 68%, 0 to 1 part of H2SO4 with a mass fraction of 95% to 98%, and 1 to 4 parts of HCl with a mass fraction of 36% to 38%. Since the sulfuric acid component of the corrosion solution is concentrated sulfuric acid, hydrofluoric acid, nitric acid and concentrated sulfuric acid are first mixed during preparation, and hydrochloric acid is finally added to prevent splashing. The corrosion solution significantly accelerates the corrosion rate and improves the corrosion effect by adding the concentrated sulfuric acid component, so that the TiNi alloy shows a better corrosion effect in a short time.

[0014] The above-mentioned method for observing the corrosion of TiNi alloy grain structure is characterized in that the HF, HNO3, H2SO4 and HCl are all analytically pure reagents.

[0015] Compared with the prior art, the present invention has the following advantages:

[0016] 1. The present invention processes the TiNi alloy into a grain structure observation plane and then performs grinding, rinsing, mechanical polishing, and corrosion with a corrosive solution in sequence, so that the grain structure in the TiNi alloy is clearly and effectively displayed, with obvious grain boundaries and no obvious corrosion pits, so that it is easy to observe the grain structure and evaluate the grain size results by open field observation, thereby solving the problem that the existing TiNi alloy grain structure corrosion method is difficult to display clear grain boundaries.

[0017] 2. The corrosion observation method of the present invention is easy to operate, and the reagents and processes are non-toxic. The grain structure of the TiNi alloy can be clearly observed without any special equipment and is easy to promote.

[0018] The technical solution of the present invention is further described in detail below through the accompanying drawings and embodiments. BRIEF DESCRIPTION OF THE DRAWINGS

[0019] Figure 1 This is the grain structure diagram of the TiNi alloy in Example 1 of the present invention.

[0020] Figure 2 This is the grain structure diagram of the TiNi alloy in Example 2 of the present invention.

[0021] Figure 3 This is the grain structure diagram of the TiNi alloy in Example 3 of the present invention.

[0022] Figure 4 This is the grain structure diagram of the TiNi alloy in Example 4 of the present invention.

[0023] Figure 5 This is the grain structure diagram of the TiNi alloy in Example 5 of the present invention.

[0024] Figure 6 This is the grain structure diagram of the TiNi alloy in Example 6 of the present invention.

[0025] Figure 7 This is the grain structure diagram of the TiNi alloy in Example 7 of the present invention. DETAILED DESCRIPTION

[0026] Example 1

[0027] This embodiment includes the following steps:

[0028] Step 1: Mechanically process the TiNi alloy to obtain a grain structure observation plane, and then grind the machined grain structure observation plane on a metallographic grinder, and wash away the sand on the grain structure observation plane after grinding; the specific process of the grinding is: using a particle size of 120 # , 400 # , 800# and 1000 # Grind step by step with metallographic water sandpaper. Each time you change the metallographic water sandpaper for grinding, turn the grinding direction 90° to ensure that the last grinding marks are completely eliminated.

[0029] Step 2: placing the grain structure observation plane washed away from the sand in step 1 on a polishing machine for mechanical polishing until there are no scratches and drags on the surface of the grain structure observation plane; the mechanical polishing is first polished with a diamond suspension with a particle size of 10 μm, and then polished with a SiO2 suspension with a particle size of 0.5 μm;

[0030] Step 3, immersing the mechanically polished grain structure observation plane in step 2 into a corrosion solution for 10 seconds; the corrosion solution is composed of the following components in volume fractions: 2 parts of HF with a mass fraction of more than 40%, 1 part of HNO3 with a mass fraction of 65% to 68%, 1 part of H2SO4 with a mass fraction of 95% to 98%, and 4 parts of HCl with a mass fraction of 36% to 38%, and HF, HNO3, H2SO4 and HCl are all analytically pure reagents;

[0031] Step 4: Place the grain structure observation plane after etching in step 3 under a metallographic microscope, and observe the grain structure by open field observation.

[0032] Figure 1 is the grain structure diagram of the TiNi alloy in this embodiment, Figure 1 The irregular lines in the figure are grain boundaries, and the black particles are the precipitation phases of TiNi alloy. Figure 1 It can be seen that the metallographic structure of the TiNi alloy has obvious grain structure and no obvious corrosion pits.

[0033] Example 2

[0034] This embodiment includes the following steps:

[0035] Step 1: Mechanically process the TiNi alloy to obtain a grain structure observation plane, and then grind the machined grain structure observation plane on a metallographic grinder, and wash away the sand on the grain structure observation plane after grinding; the specific process of the grinding is: using a particle size of 120 # , 400 # , 800# and 1000 #Grind step by step with metallographic water sandpaper. Each time you change the metallographic water sandpaper for grinding, turn the grinding direction 90° to ensure that the last grinding marks are completely eliminated.

[0036] Step 2: placing the grain structure observation plane washed away from the sand in step 1 on a polishing machine for mechanical polishing until there are no scratches and drags on the surface of the grain structure observation plane; the mechanical polishing is first polished with a diamond suspension with a particle size of 10 μm, and then polished with a SiO2 suspension with a particle size of 0.5 μm;

[0037] Step 3, immersing the mechanically polished grain structure observation plane in step 2 into a corrosion solution for 8 seconds; the corrosion solution is composed of the following components in volume fractions: 2 parts of HF with a mass fraction of more than 40%, 0.5 parts of HNO3 with a mass fraction of 65% to 68%, 0.5 parts of H2SO4 with a mass fraction of 95% to 98%, and 2 parts of HCl with a mass fraction of 36% to 38%, and HF, HNO3, H2SO4 and HCl are all analytically pure reagents;

[0038] Step 4: Place the grain structure observation plane after etching in step 3 under a metallographic microscope, and observe the grain structure by open field observation.

[0039] Figure 2 is the grain structure diagram of the TiNi alloy in this embodiment, Figure 2 The irregular lines in the figure are grain boundaries, and the black particles are the precipitation phases of TiNi alloy. Figure 2 It can be seen that the metallographic structure of the TiNi alloy has obvious grain structure and no obvious corrosion pits.

[0040] Example 3

[0041] This embodiment includes the following steps:

[0042] Step 1: Mechanically process the TiNi alloy to obtain a grain structure observation plane, and then grind the machined grain structure observation plane on a metallographic grinder, and wash away the sand on the grain structure observation plane after grinding; the specific process of the grinding is: using a particle size of 120 # , 400 # , 800# and 1000 # Grind step by step with metallographic water sandpaper. Each time you change the metallographic water sandpaper for grinding, turn the grinding direction 90° to ensure that the last grinding marks are completely eliminated.

[0043] Step 2: placing the grain structure observation plane washed away from the sand in step 1 on a polishing machine for mechanical polishing until there are no scratches and drags on the surface of the grain structure observation plane; the mechanical polishing is first polished with a diamond suspension with a particle size of 10 μm, and then polished with a SiO2 suspension with a particle size of 0.5 μm;

[0044] Step 3, immersing the mechanically polished grain structure observation plane in step 2 into a corrosion solution for 6 seconds; the corrosion solution is composed of the following components in volume fractions: 2 parts of HF with a mass fraction of more than 40%, 1 part of HNO3 with a mass fraction of 65% to 68%, 1 part of H2SO4 with a mass fraction of 95% to 98%, and 2 parts of HCl with a mass fraction of 36% to 38%, and HF, HNO3, H2SO4 and HCl are all analytically pure reagents;

[0045] Step 4: Place the grain structure observation plane after etching in step 3 under a metallographic microscope, and observe the grain structure by open field observation.

[0046] Figure 3 is the grain structure diagram of the TiNi alloy in this embodiment, Figure 3 The irregular lines in the figure are grain boundaries, and the black particles are the precipitation phases of TiNi alloy. Figure 3 It can be seen that the metallographic structure of the TiNi alloy has obvious grain structure and no obvious corrosion pits.

[0047] Example 4

[0048] This embodiment includes the following steps:

[0049] Step 1: Mechanically process the TiNi alloy to obtain a grain structure observation plane, and then grind the machined grain structure observation plane on a metallographic grinder, and wash away the sand on the grain structure observation plane after grinding; the specific process of the grinding is: using a particle size of 120 # , 400 # , 800# and 1000 # Grind step by step with metallographic water sandpaper. Each time you change the metallographic water sandpaper for grinding, turn the grinding direction 90° to ensure that the last grinding marks are completely eliminated.

[0050] Step 2: placing the grain structure observation plane washed away from the sand in step 1 on a polishing machine for mechanical polishing until there are no scratches and drags on the surface of the grain structure observation plane; the mechanical polishing is first polished with a diamond suspension with a particle size of 10 μm, and then polished with a SiO2 suspension with a particle size of 0.5 μm;

[0051] Step 3, immersing the mechanically polished grain structure observation plane in step 2 into a corrosion solution for 12 seconds; the corrosion solution is composed of the following components in volume fractions: 1 part of HF with a mass fraction of more than 40%, 2 parts of HNO3 with a mass fraction of 65% to 68%, 1 part of H2SO4 with a mass fraction of 95% to 98%, and 4 parts of HCl with a mass fraction of 36% to 38%, and HF, HNO3, H2SO4 and HCl are all analytically pure reagents;

[0052] Step 4: Place the grain structure observation plane after etching in step 3 under a metallographic microscope, and observe the grain structure by open field observation.

[0053] Figure 4 is the grain structure diagram of the TiNi alloy in this embodiment, Figure 4 The irregular lines in the figure are grain boundaries, and the black particles are the precipitation phases of TiNi alloy. Figure 4 It can be seen that the metallographic structure of the TiNi alloy has obvious grain structure and no obvious corrosion pits.

[0054] Example 5

[0055] This embodiment includes the following steps:

[0056] Step 1: Mechanically process the TiNi alloy to obtain a grain structure observation plane, and then grind the machined grain structure observation plane on a metallographic grinder, and wash away the sand on the grain structure observation plane after grinding; the specific process of the grinding is: using a particle size of 120 # , 400 # , 800# and 1000 # Grind step by step with metallographic water sandpaper. Each time you change the metallographic water sandpaper for grinding, turn the grinding direction 90° to ensure that the last grinding marks are completely eliminated.

[0057] Step 2: placing the grain structure observation plane washed away from the sand in step 1 on a polishing machine for mechanical polishing until there are no scratches and drags on the surface of the grain structure observation plane; the mechanical polishing is first polished with a diamond suspension with a particle size of 10 μm, and then polished with a SiO2 suspension with a particle size of 0.5 μm;

[0058] Step 3, immersing the mechanically polished grain structure observation plane in step 2 into a corrosion solution for 20 seconds; the corrosion solution is composed of the following components in volume fractions: 2 parts of HF with a mass fraction of more than 40%, 2 parts of HNO3 with a mass fraction of 65% to 68%, and 4 parts of HCl with a mass fraction of 36% to 38%, and HF, HNO3, H2SO4 and HCl are all analytically pure reagents;

[0059] Step 4: Place the grain structure observation plane after etching in step 3 under a metallographic microscope, and observe the grain structure by open field observation.

[0060] Figure 5 is the grain structure diagram of the TiNi alloy in this embodiment, Figure 5 The irregular lines in the figure are grain boundaries, and the black particles are the precipitation phases of TiNi alloy. Figure 5 It can be seen that the metallographic structure of the TiNi alloy has obvious grain structure and no obvious corrosion pits.

[0061] Example 6

[0062] This embodiment includes the following steps:

[0063] Step 1: Mechanically process the TiNi alloy to obtain a grain structure observation plane, and then grind the machined grain structure observation plane on a metallographic grinder, and wash away the sand on the grain structure observation plane after grinding; the specific process of the grinding is: using a particle size of 120 # , 400 # , 800# and 1000 # Grind step by step with metallographic water sandpaper. Each time you change the metallographic water sandpaper for grinding, turn the grinding direction 90° to ensure that the last grinding marks are completely eliminated.

[0064] Step 2: placing the grain structure observation plane washed away from the sand in step 1 on a polishing machine for mechanical polishing until there are no scratches and drags on the surface of the grain structure observation plane; the mechanical polishing is first polished with a diamond suspension with a particle size of 10 μm, and then polished with a SiO2 suspension with a particle size of 0.5 μm;

[0065] Step 3, immerse the mechanically polished grain structure observation plane in step 2 into a corrosion solution for 5 seconds; the corrosion solution is composed of the following components by volume: 4 parts of HF with a mass fraction of more than 40%, 2 parts of HNO3 with a mass fraction of 65% to 68%, 1 part of H2SO4 with a mass fraction of 95% to 98%, and 4 parts of HCl with a mass fraction of 36% to 38%, and HF, HNO3, H2SO4 and HCl are all analytically pure reagents;

[0066] Step 4: Place the grain structure observation plane after etching in step 3 under a metallographic microscope, and observe the grain structure by open field observation.

[0067] Figure 6 is the grain structure diagram of the TiNi alloy in this embodiment, Figure 6 The irregular lines in the figure are grain boundaries, and the black particles are the precipitation phases of TiNi alloy. Figure 6It can be seen that the metallographic structure of the TiNi alloy has obvious grain structure and no obvious corrosion pits.

[0068] Example 7

[0069] This embodiment includes the following steps:

[0070] Step 1: Mechanically process the TiNi alloy to obtain a grain structure observation plane, and then grind the machined grain structure observation plane on a metallographic grinder, and wash away the sand on the grain structure observation plane after grinding; the specific process of the grinding is: using a particle size of 120 # , 400 # , 800# and 1000 # Grind step by step with metallographic water sandpaper. Each time you change the metallographic water sandpaper for grinding, turn the grinding direction 90° to ensure that the last grinding marks are completely eliminated.

[0071] Step 2: placing the grain structure observation plane washed away from the sand in step 1 on a polishing machine for mechanical polishing until there are no scratches and drags on the surface of the grain structure observation plane; the mechanical polishing is first polished with a diamond suspension with a particle size of 10 μm, and then polished with a SiO2 suspension with a particle size of 0.5 μm;

[0072] Step 3, immersing the mechanically polished grain structure observation plane in step 2 into a corrosion solution for 10 seconds; the corrosion solution is composed of the following components by volume: 2 parts of HF with a mass fraction of more than 40%, 1 part of HNO3 with a mass fraction of 65% to 68%, 1 part of H2SO4 with a mass fraction of 95% to 98%, and 1 part of HCl with a mass fraction of 36% to 38%, and HF, HNO3, H2SO4 and HCl are all analytically pure reagents;

[0073] Step 4: Place the grain structure observation plane after etching in step 3 under a metallographic microscope, and observe the grain structure by open field observation.

[0074] Figure 7 is the grain structure diagram of the TiNi alloy in this embodiment, Figure 7 The irregular lines in the figure are grain boundaries, and the black particles are the precipitation phases of TiNi alloy. Figure 7 It can be seen that the metallographic structure of the TiNi alloy has obvious grain structure and no obvious corrosion pits.

[0075] The above is only a preferred embodiment of the present invention and does not limit the present invention in any way. Any simple modification, change and equivalent change made to the above embodiment according to the technical essence of the invention still falls within the protection scope of the technical solution of the present invention.

Claims

1. A corrosion observation method for TiNi alloy grain structure, characterized in that: The method comprises the following steps: Step 1, machining a TiNi alloy to obtain a grain structure observation plane, then grinding the machined grain structure observation plane on a metallographic grinder, and washing away the sand on the grain structure observation plane after grinding; Step 2: placing the grain structure observation plane from which the sand has been washed off in step 1 on a polishing machine for mechanical polishing until there are no scratches or drag on the surface of the grain structure observation plane; Step 3, immersing the mechanically polished grain structure observation plane in step 2 into a corrosive solution for 5s to 20s; Step 4: Place the grain structure observation plane after etching in step 3 under a metallographic microscope, and observe the grain structure by open field observation.

2. The corrosion observation method of TiNi alloy grain structure according to claim 1, characterized in that: The specific process of grinding in step 1 is: using a particle size of 120 # , 400 # , 800# and 1000 # The metallographic water sandpaper is used for grinding step by step. Each time the metallographic water sandpaper is changed for grinding, the grinding direction is turned 90° to ensure that the previous grinding marks are completely eliminated.

3. The corrosion observation method of TiNi alloy grain structure according to claim 1, characterized in that: The mechanical polishing in step 2 is first performed using a diamond suspension with a particle size of 10 μm, and then performed using a SiO2 suspension with a particle size of 0.5 μm.

4. The corrosion observation method of TiNi alloy grain structure according to claim 1, characterized in that: The etching solution in step 3 is composed of the following components in parts by volume: 1 to 2 parts of HF with a mass fraction of more than 40%, 0.5 to 2 parts of HNO3 with a mass fraction of 65% to 68%, 0 to 1 part of H2SO4 with a mass fraction of 95% to 98%, and 1 to 4 parts of HCl with a mass fraction of 36% to 38%.

5. The corrosion observation method of TiNi alloy grain structure according to claim 4, characterized in that: The HF, HNO3, H2SO4 and HCl are all analytically pure reagents.